Diffusion of a systemic innovation: A longitudinal case study of a Swedish multi-storey timber housebuilding system. Issue 1 (3rd January 2017) - Lindgren, John; Emmitt, Stephen
Abstract : Purpose: The purpose of this paper is to identify factors that influence the diffusion of a systemic innovation in the Swedish construction sector. The focus is on high-rise multi-storey timber housing; the development of which was enabled by a change in building regulations. This allowed building higher than two stories in timber. Design/methodology/approach: A longitudinal case study was used with multiple data collection methods to study the development and diffusion of a multi-storey timber house system by a case study organisation. Findings: The findings contribute to understanding for a number of interacting factors influencing the diffusion of a systemic innovation related to the case study organisation. Originality/value: The research provides a holistic view of interacting factors influencing the diffusion of a systemic innovation. The results have value to the Swedish construction sector and to the global community of construction researchers, as it provides empirical findings that further increase the understanding for diffusion of systemic innovations in a specific context.